Resolving Optimum Magnetic Signatures for Drill-Hole Targeting in Gold Exploration – A Case Study for Mbudzane in Gwanda, Zimbabwe - Hlatywayo, Dumisani John; Sakala, Emmanuel (International Journal of Geography and Geology, 2013)
Optimum magnetic signatures for drill-hole targeting in gold exploration in Mbudzane were resolved from induced polarisation-resistivity and magnetic anomalies. Total magnetic field and a gold-in-soil map showed the area is magnetically quiet with high anomalous values along old gold workings. Induced polarisation was carried out along a grid for lines of 500m length, 50m separation and a baseline oriented at 330˚. The survey comprised a gradient array and three real sections. The magnetic survey was conducted over the same grid as the induced polarisation. Stations were set at 5m intervals for a line spacing of 50m. The results show intense anomalies that suggest different degrees of magnetic alteration and a set of conjugate lineaments and faults that possibly control the mineralisation in Mbudzane. The tilt derivative of the reduced-to-pole image resolves the separation between anomalies, giving information on the faulting. High chargeability is confined to the sheared and silicified mafic schist. The gradient resistivity image revealed contact between rock formations. Real section IP shows coincident low chargeability – low resistivity anomalies close to the surface. Chargeability intensity increases with depth, suggesting incipient development of disseminated sulphide replacement zones. A strong correlation between ground magnetic inferred contacts and apparent resistivity-chargeability anomalies forms the basis for suggesting a new drill-hole targeting. They dictate both the depth and angle at which drilling should be carried out. These results should be applicable to any region where drill-hole targeting in gold exploration may be required.